1978
DOI: 10.1139/m78-259
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic and protective activity associated with a lipopolysaccharide from Coxiella burnetii

Abstract: A purified lipopolysaccharide (LPS) isolated from the rickettsial agent of Q fever, Coxiella burnetii phase 1, possesses some of the in vivo and in vitro biological properties previously only associated with bacterial endotoxins. The Coxiella LPS is mitogenic for guinea pig leukocytes, induces non-specific resistance in mice to virulent Candida albicans, causes dermal Schwartzman reactions, and is positive by the limulus lysate assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recently we reported that exposure of the lysate to LPS I results in gelation (Paquet et al 1978). When the limulus lysate was exposed to subnanogram amounts of LPS 11, it too induced gelation (Fig.…”
Section: Limulus Lysate Activity Of Lps 11mentioning
confidence: 86%
“…Recently we reported that exposure of the lysate to LPS I results in gelation (Paquet et al 1978). When the limulus lysate was exposed to subnanogram amounts of LPS 11, it too induced gelation (Fig.…”
Section: Limulus Lysate Activity Of Lps 11mentioning
confidence: 86%
“…Phase II LPS was extracted from cloned as well as noncloned phase II cells which had been serially passaged 95 times through embryonated eggs. Complement fixation and immunodiffusion tests indicated immunological identity of both LPS species (152). Characteristic of other bacterial LPS, phase I and II LPS caused gelation of Limulus lysates; phase I LPS induced DNA synthesis in guinea pig leukocytes, nonspecific resistance in mice to virulent Candida albicans, and the dermal Schwartzman reaction (152,176).…”
Section: Phase Variationmentioning
confidence: 98%
“…Complement fixation and immunodiffusion tests indicated immunological identity of both LPS species (152). Characteristic of other bacterial LPS, phase I and II LPS caused gelation of Limulus lysates; phase I LPS induced DNA synthesis in guinea pig leukocytes, nonspecific resistance in mice to virulent Candida albicans, and the dermal Schwartzman reaction (152,176). Thirteen of the 14 sugars found in phase I LPS were also present in phase II LPS, although some of the sugars were present in different proportions (i.e., glucose comprised 20% of the total phase I neutral sugars, but only 2 to 3% of the phase II neutral sugars).…”
Section: Phase Variationmentioning
confidence: 98%
“…Although the connection is highly speculative, the observed placental lesions are reminiscent of changes described as a local Schwartzman-like reaction following administration of endotoxin (13,17,29,51). Some biological activities associated with gram-negative bacterial endotoxin are elicited by C. burnetii lipopolysaccharide (LPS) (5), but compared with other pathogens, Coxiella LPS can be classified as a poor endotoxin (2,16,33,42,43), and large quantities of purified C. burnetii LPS are necessary to induce endotoxic changes (31). Many biological activities once attributed directly to LPS are now known to be mediated by LPS-induced cytokines.…”
Section: *~~~~Tmentioning
confidence: 99%